Towards an instrument for surveying knowledge management practices - D. F. Botha (South African Journal of Business Management, 2005)
The research was conducted to develop and stabilize a data collection and analysis instrument for an annual survey of knowledge management practices in the South African business sector. From a literature study it was deduced that six factors could be identified with necessary and sufficient reason to be used as main parameters for the assessment instrument. Synthesized a priori and posteriori judgmental knowledge was used to construct a number of aggregational indicators for each factor. Each indicator posited as a statement being a recognized knowledge management practice. A modified six point Likert scale was created to score/indicate gradual progression towards full implementation of a specific practice. Regression factor analysis and one-way analysis of variance was used on the collected data to evaluate the instrument. These analyses indicated that the instrument could detect the expected differences on the demographics and on the KM practices of the survey and could therefore be declared sound and verified. The analyses also revealed several modifications that could be used to improve the instrument.
Keywords: 650